Transition into distance education: A scoping review protocol. - Roxana Schweighart; Michael Hast; Caroline Trautwein (PLoS ONE)
The number of students choosing to complete their studies online rather than in-person is on the rise. The transition to university is crucial for subsequent success, regardless of whether the learning is done face-to-face or remotely. If students can effectively handle the critical requirements associated with the transition to distance learning, their likelihood of success increases. However, thus far, little information is available on this topic. To gather existing sources, we will conduct a scoping review according to the guidelines of the research organization JBI. The review aims to systematically record, evaluate, and subsequently present the existing body of literature regarding the subject "transition into distance education". By answering the research question, "What is known about transition into distance education in higher education?" we hope to shed light on individual experiences, challenges, adaptation strategies, life situations, etc. of distance learners in a higher education context. The review will identify and categorize relevant concepts and terminologies in the research field, as well as outline the content-related boundaries. The findings derived from the scoping review will provide conceptual clarification, summarize the given theoretical and empirical knowledge in the field and offer practical implications for designing the initial phase in distance education. This article presents the a-priori study protocol that provides a detailed outline of the planned methodology for conducting the Scoping Review.